151k views
1 vote
What are the steps to understanding this problem as well as the answers.

What are the steps to understanding this problem as well as the answers.-example-1

1 Answer

4 votes

Explanation:

1


(1)/(3 + 4i) * (3 - 4i)/(3 - 4i) = (3 - 4i)/(25) = ( 3)/(25) - (4i)/(25)

2)


(1)/(3 - 4i) * (3 + 4i)/(3 + 4i) = (3 + 4i)/(25) = ( 3)/(25) + (4i)/(25)

3)

1+0i

4)


(3 - 4i)/(3 + 4i) * (3 - 4i)/(3 - 4i) = ( - 7 - 24i)/(25) = - (7)/(25) - (24i)/(25)

5)

3 - 4i

6)


(3 + 4i)/(3 - 4i) * (3 + 4i)/(3 + 4i) = ( - 7 + 24i)/(25) = - (7)/(25) + (24i)/(25)

User Simply Brian
by
4.7k points